THE EFFECTS OF WILSON READING SYSTEM ON UPPER ELEMNTARY SCHOOL STUDENTS WITH A LEARNING DISABILITY IN READING FLUENCY - Gentry, Ashley Heath (East Carolina University, 2019)
Schools throughout the United States struggle to meet the needs of students with a deficit in reading. Experimental research showing the effectiveness of the Wilson Reading System is lacking enough evidence. This study examined the effectiveness of a seven-week intervention with the Wilson Reading System implemented in an elementary school in a rural county in a state in the southeast United States. The study included six students with learning disabilities in reading fluency. A quasi-experimental pretest-posttest research design was used to determine the effectiveness of the Wilson Reading System on students with learning disabilities in reading fluency. This was done by examining the differences in reading performance following the completion of seven weeks of intervention using the Wilson Reading System. The Dynamic Indicators of Basic Early Literacy Skills assessment was used to measure the differences in reading performance before and throughout the intervention. A t-test analysis was used with student's Dynamic Indicators of Basic Early Literacy Skills scores from the pretest and posttest. The study showed a statistical difference for many students on several measures (p<.05). Based on expected rate of improvement as set by Dynamic Indicators of Basic Early Literacy Skills, three students exceeded Rate of Improvement for Oral Reading Fluency Accuracy and Fluency, five students exceeded Rate of Improvement for Nonsense Word Fluency Correct Letter Sounds, and three students exceeded Rate of Improvement for Nonsense Word Fluency Whole Words Read. These findings suggest that the results of most students show success with the Wilson Reading System, although other factors may impact student progression in the program. This study contributes to positive educational changes as it shows the limited information gained by short-term intervention programs and brings to light the extensive effort needed to address reading deficits for students with learning disabilities in reading fluency.
Keywords: reading fluency; Wilson Reading System; Reading--Ability testing--Southern States; Learning disabilities--Southern States